Morphological Processes of Social Media Neologisms - Shahlee, Shakina; Ahmad, Salawati (Development in Language Studies, 2022)
Morphology is a study of word formation and coinage. This research investigated the morphological processes used in wide usage and development of neologisms through selected social media platforms namely, Facebook, Instagram and Twitter. This study is a textual based analysis through qualitative approach. The samples were collected by random sampling of selecting social media influencers within the computer-mediated communication as the neologisms analysed evolved in a wide platform due to online social media. The aspect of morphological process and word classes of the neologisms were analysed by using lexical semantics analysis. The results indicate that acronym was the most common used of new word formation and most new words were formed in noun class through social media in this era. New word formation was found in this study as the sequence formation of words was undefined and it is named as reposition. The result demonstrated that language is evolving occasionally and it is significant to language researchers and users to increase awareness to the language changes usage on social media platforms in terms of morphological structures and neologisms.